Alcohol consumption by breastfeeding mothers: Frequency, correlates and infant outcomes. (13th March 2017) - Wilson, Judy; Tay, Rui Yang; McCormack, Clare; Allsop, Steve; Najman, Jake; Burns, Lucy; Olsson, Craig A.; Elliott, Elizabeth; Jacobs, Sue; Mattick, Richard P.; Hutchinson, Delyse
Abstract: Introduction and Aims: There is limited research regarding the effects of alcohol consumption by breastfeeding mothers on infant development. This study examined the frequency, correlates and outcomes of alcohol use during lactation. Design and Methods: Data were from an Australian cohort study. Maternal demographics and substance use were assessed during pregnancy and at 8 weeks and 12 months postpartum. Breastfeeding duration, infant feeding, sleeping and development (Ages and Stages Questionnaire) were also assessed postpartum. Logistic regression and general linear model analyses examined characteristics of women who drank during breastfeeding, and the association between alcohol use during breastfeeding and infant outcomes. Results: Alcohol use was reported by 60.7% and 69.6% of breastfeeding women at 8 weeks and 12 months postpartum, respectively. Breastfeeding women who consumed alcohol were more likely to be born in Australia or another English‐speaking country, be tertiary educated and have higher household incomes. Most drank at low levels (≤14 standard drinks per week, <3 per occasion) and employed strategies (e.g. timing of alcohol use) to minimise alcohol passed onto infants via breastmilk. Alcohol consumption was unrelated to breastfeeding duration, infant feeding and sleeping behaviour at 8 weeks, and most infant developmental outcomes at 8 weeks or 12 months, after adjusting for confounders. The only significant association showed that infants whose mothers drank at 8 weeks postpartum had more favourable results for personal‐social development at 12 months compared with those whose mothers abstained. Discussion and Conclusions: Low level drinking during breastfeeding is not linked with shorter breastfeeding duration or adverse outcomes in infants up to 12 months of age. [Wilson J, Tay RY, McCormack C, Allsop S, Najman J, Burns L, Olsson CA, Elliott E, Jacobs S, Mattick RP, Hutchinson D. Alcohol consumption by breastfeeding mothers: Frequency, correlates and infant outcomes. Drug Alcohol Rev 2017;00:000‐000]